The identity of Ligularia emeiensis (Asteraceae, Senecioneae), a name overlooked since its publication - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2017)
Ligularia emeiensis (Asteraceae, Senecioneae), which was described in 1991 from Emei Shan, Sichuan, China, has been overlooked and not treated even in the account of the genus Ligularia in the Flora of China published in 2011. It is found to be identical with L. dentata subsp. sutchuenensis and is thus synonymized herein.